Lipid-lowering nutraceuticals in clinical practice: position paper from an International Lipid Expert Panel - Cicero, Arrigo F G; Colletti, Alessandro; Bajraktari, Gani; Descamps, Olivier; Djuric, Dragan M; Ezhov, Marat; Fras, Zlatko; Katsiki, Niki; Langlois, Michel; Latkovskis, Gustavs; Panagiotakos, Demosthenes B; Paragh, Gyorgy; et al. (Nutrition reviews, 2017)
In recent years, there has been growing interest in the possible use of nutraceuticals to improve and optimize dyslipidemia control and therapy. Based on the data from available studies, nutraceuticals might help patients obtain theraputic lipid goals and reduce cardiovascular residual risk. Some nutraceuticals have essential lipid-lowering properties confirmed in studies; some might also have possible positive effects on nonlipid cardiovascular risk factors and have been shown to improve early markers of vascular health such as endothelial function and pulse wave velocity. However, the clinical evidence supporting the use of a single lipid-lowering nutraceutical or a combination of them is largely variable and, for many of the nutraceuticals, the evidence is very limited and, therefore, often debatable. The purpose of this position paper is to provide consensus-based recommendations for the optimal use of lipid-lowering nutraceuticals to manage dyslipidemia in patients who are still not on statin therapy, patients who are on statin or combination therapy but have not achieved lipid goals, and patients with statin intolerance. This statement is intended for physicians and other healthcare professionals engaged in the diagnosis and management of patients with lipid disorders, especially in the primary care setting.
Keywords: intestinální absorpce; Liver; Randomized Controlled Trials as Topic; Probiotics; fytonutrienty; Intestinal Absorption; lékové interakce; LDL-cholesterol; játra; Drug Interactions; Dyslipidemias; Cholesterol, LDL; position paper; triglyceridy; Life Style; životní styl; Dietary Supplements; Triglycerides; lidé; potravní doplňky; Fatty Acids, Unsaturated; statiny; Humans; Risk Factors; Observational Studies as Topic; pozorovací studie jako téma; Cardiovascular Diseases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; recommendations; probiotika; nenasycené mastné kyseliny; Meta-Analysis as Topic; medicína založená na důkazech; lipid; dyslipidemie; HDL-cholesterol; randomizované kontrolované studie jako téma; rizikové faktory; kardiovaskulární nemoci; dyslipidemia; Phytochemicals; nutraceuticals; Evidence-Based Medicine; metaanalýza jako téma; Cholesterol, HDL